The Existence of "Unmastered Cultural Heritage": The Art of Cirebon Masks in the Midst of the Flow of Tourists Instagram able - Agung Setiawan; Tia Listiyati (Jurnal Toursci, 2025)
Background. The Cirebon Mask Dance, an Intangible Cultural Heritage (WBTB) of Indonesia that is rich in philosophical values, is now at a crucial crossroads. On the one hand, there are internal challenges related to the regeneration and transmission of knowledge. On the other hand, the wave of digital tourism, mediated by visual platforms such as Instagram, presents massive commodification pressure. This phenomenon transforms cultural representations from holistic narratives into aesthetic fragments curated for quick consumption in the digital space, or popularly referred to as Instagramable content. Purpose. This research aims to unravel the dialectic between the efforts to preserve authenticity by the artist community and the commodification forces at work in the digital tourism ecosystem. Using the critical phenomenological framework of Pierre Bourdieu, this study will examine how symbolic capital (cultural authenticity) is negotiated, transformed, and even reduced in the digital tourism 'arena'. This study fills the research gap by not only focusing on the impact of tourism, but also analyzing the mechanisms of symbolic violence that occur when digital aesthetics dominate and shape tourist perceptions, potentially eroding the sacred and philosophical meaning of the Cirebon Mask Dance. Method. This study adopts a qualitative approach with a multisite case study design. Data collection will be carried out through a hybrid method that combines (1) Netnography and Visual Content Analysis (VCA) on the Instagram platform to map patterns of representation and digital commodification, and (2) In-depth interviews and participatory observations with dance maestros, young artists, studio managers, and tourism stakeholders in Cirebon. Triangulation of data from the virtual world and field reality will be analyzed thematically to uncover tensions, adaptation strategies, and emerging forms of cultural resistance. Results. The results of this study are expected to make three main contributions. Theoretically, this research will produce a conceptual model of WBTB's cultural resilience in the face of digital commodification. Conclusion. In practical terms, these findings will form the basis for the formulation of digital literacy modules aimed at the artist community, equipping them with the tools to manage their own cultural representations. In terms of policy, this research will produce a policy brief that provides strategic recommendations for local governments to develop sustainable cultural tourism, which balances between economic promotion and preservation of cultural dignity.